Hegemony, Personality, and Network: Kyai Versus Kyai in Sumenep Local Election 2024 - Sefina, Agnina Delia; Chalik, Abdul; Mahjumi, Muhammad Haekal Ali (UIN Sunan Ampel Surabaya, 2025)
The local political contest in Sumenep in 2024 is not just an ordinary electoral competition, but rather a field of tug-of-war of hegemony between charismatic figures who are both kyais. This phenomenon suggests that local political dynamics are not solely influenced by the political party machine but are also driven by three primary pillars: religious hegemony, charismatic personality, and interconnected socio-political networks. In this context, kyais become the epicenter that is difficult to change by an additional power, where kyais’ standing is not merely a political power but also determines triumph through social power with the santri network and alumni. This article discusses how kyai personalities are formed and contested within the arena of local control. Kyai, who is usually used as a spiritual role model, is now involved as a strategic actor in the electoral political space. With a qualitative and quantitative approach, and data collected from interviews, observations, and documentation, these findings demonstrate that the personal charisma of the kyai is not isolated but is also strengthened by social networks, pesantren relationships, and pragmatic political affiliations. The Sumenep Election reveals a symbolic battle between moral authority, socio-religious values, and the power of patronage networks.